1988
DOI: 10.1007/bf00278756
|View full text |Cite
|
Sign up to set email alerts
|

Improved metabolic control does not alter the charge-dependent glomerular filtration of albumin in uncomplicated Type 1 (insulin-dependent) diabetes

Abstract: The selectivity index, i.e. clearance of non glycated albumin/clearance of glycated albumin was studied in fourteen patients with Type 1 (insulin-dependent) diabetes and normal urinary albumin excretion. The index was increased above one in all patients, and correlated significantly to HbA1c. It was, however, unaffected by 12 weeks of improved metabolic control with a mean decline in HbA1c of 1.9% in seven patients. We conclude that the increased electronegative charge of the glomerular filtration barrier obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In contrast, diabetic patients showed a 30 % higher clearance of nonglycated albumin combined with a slightly higher clearance of glycated albumin, resulting in a mean selectivity index significantly higher than in normal subjects. This finding indicates that in normoalbuminuric diabetic patients the renal excretion of glycated albumin is relatively lower than that of non-glycated albumin, as previously documented by Kverneland et al [7,8] on 24-h urine collection during normal physical activity. On the other hand, our results and those of Kverneland et al disagree with the preferential urinary excretion of glycated proteins reported by others [5,6] using a method considered as poorly specific for glycated albumin [17].…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, diabetic patients showed a 30 % higher clearance of nonglycated albumin combined with a slightly higher clearance of glycated albumin, resulting in a mean selectivity index significantly higher than in normal subjects. This finding indicates that in normoalbuminuric diabetic patients the renal excretion of glycated albumin is relatively lower than that of non-glycated albumin, as previously documented by Kverneland et al [7,8] on 24-h urine collection during normal physical activity. On the other hand, our results and those of Kverneland et al disagree with the preferential urinary excretion of glycated proteins reported by others [5,6] using a method considered as poorly specific for glycated albumin [17].…”
Section: Discussionsupporting
confidence: 78%
“…The increment was most pronounced after 6 and 12 months. One previous study investigated prospectively the influence of strict metabolic control during 12 weeks using non-glycated/glycated albumin as a selectivity index [17]. Their subjects were normoalbuminuric and no effect of strict metabolic control was observed.…”
Section: Discussionmentioning
confidence: 99%
“…By measuring the renal clearance of pairs of plasma proteins which differ in charge but not in molecular size, alterations of the charge selectivity of the GBM can be identified. We have used nonglycated and glycated albumin [61,621, glycated albumin being more negatively charged in comparison to nonglycated [62]. We have also used neutral IgG and the anionic charged IgG4 fraction [64, 651. The ratio between the clearance of the less anionic and the more anionic plasma proteins is the selectivity index (SI).…”
Section: Alteration Of the Composition Of The Extracellular Matrixmentioning
confidence: 99%